THE REBURIAL OF IMAM GAZIMUHAMMAD: RECONSTRUCTION OF EVENTS (1832-1843) - Tahnaeva, Patimat Ibragimovna (History, Archeology and Ethnography of the Caucasus, 2022)
The article presents a microstudy on reconstruction of the history of the burial (1832) and reburial (1843) of Imam Gazimuhammad (1795-1832). The study is based on known local and Russian sources, as well as new little-known sources, with the introduction of local-history material and folklore. Reconstruction of the history of the reburial of the Imam (1832-1843) allows to address a relevant question in connection with the reburial (2019) of Naib Hadji Murad about the precedents and admissibility of the reburial of Muslims, in particular, in the Imamate. A number of speculations that have been circulating among local authors related to the burial of the imam are subjected to critical revision: that imam Gazimuhammad was transferred from the village of Gimry for burial in the city of Tarki (Ukrainian: Burnaya) at the insistence of Said of Arakan (in order to avoid veneration of his grave); about the fact that the body of the deceased, before it was buried, had been humiliated, dissected in some way (salted and dried); that after the burial, the traces of the Imam’s grave were deliberately erased and its location remained unknown, but was guarded by soldiers. Local authors name different individuals who took the initiative to rebury the body of Imam Gazimuhammad in 1843, but all sources are unanimous in their assertion that the reburial took place under the control of Imam Shamil and by his order. The author of the well-known image of the half-naked body of the deceased Imam was a participant of the storming of Gimry P.A. Bestuzhev-Ryumin. The fact that the author made the image of the body of the real Imam is seriously questionable. The posture of the murdered Imam captured by the author (“with one hand he held his beard, and with the other he pointed to the sky”), which in Russian sources seemed sacred to Muslims and did not avoid conspiracy theories, does not stand up to criticism. It was possible to identify a resident of the village of Kyakhulay “Haji Atak b. Giraykhan al-Kahuliy”, Asadula Gereykhanov (born 1872), who erected a monument on the site of the former grave of Imam Gazimuhammad.
Keywords: Caucasian War; Imam Gazimuhammad; Gimry; burial of the imam; Imamate; Imam Shamil; Tarki; cenotaph; mausoleum of Imam Gazimuhammad